Maternalism, Co-responsibility, and Social Equity: A Typology of Work–Family Policies - Blofield, Merike (2015)
This paper provides a conceptual lens to address the complexity of policies involved in reconciling paid work and family responsibilities. Our typology classifies policies by how they intervene in the relation between paid work and family relations—by alternating paid and unpaid work, by transferring unpaid work outside the family or by formalizing home-based paid care—and by disaggregating implications for both social equity and gender relations (maternalism versus paternal or state co-responsibility) across policies. The paper makes a three-fold contribution. First, our typology looks at a set of policies rather than specific policies or overall policy regimes. Second, it helps disaggregate implications for gender and social equity. Third, it allows for comparative analysis of small and large numbers of cases across policy stages. Although we draw on Latin America,1 our typology has broader application and is especially suited to examining countries with high-income inequality.